Effectiveness Test Antidiarrhea of the Combination of Ziziphus Mauritiana Leaves and Curcuma Domestica Rhizome on Male Mice (Mus musculus) - Rita Muliyani; Andi Zsazsa Rafiatul Muklis; Nur Mahdi (Journal of Pharmacology Experiment and Pharmaceutical Technology, 2025)
Diarrhea is a disease that experiences an increase in fecal mass and the number of bowel movements is more than 4 times per day. Synthetic drugs are often used to treat diarrhea, but they often cause dangerous side effects. Bidara leaves (Ziziphus mauritiana) and turmeric rhizomes (Curcuma domestica) are often used as alternative treatments to treat diarrhea because they contain potential diarrheal drugs. The purpose of this study is to determine the antidiarrheal effect of a combination of bidara leaf ethanol extract (BLEE) and turmeric rhizome ethanol extract (TREE) on male mice that were given PO with oleum ricini. The research method used was experimental with the induction of oleum ricini diarrhea with a combination dose of EEDB and EERK 4mg:2mg/20grBB, 2mg:4mg/20grBB and 4mg:4mg/20grBB. The results of the study with One Way ANOVA with a confidence level of 95% in this study were < 0.05 which means that there was a significant difference and continued LSD tests in all combination groups obtained a meaningful difference with the positive control group (attapulgite). The results of the study concluded that the combination of bidara leaves (Ziziphus mauritiana) and turmeric rhizomes (Curcuma domestica) had a stronger antidiarrheal effect than positive control (attapulgite).